Transnational Identity in Anil’s Ghost (Pursuits: A Journal of English Studies, 2022)
Anil Tessera who is portrayed as the central character in the novel seems to be like Michael Ondaatje who is a transnational Sri Lankan and Canadian writer. Like Ondaatje, Anil carries dual citizenship. On the one hand, the novel shows how Anil returns to Sri Lanka i.e. her home country in the middle of the civil war when the government armies fight with Tamil Tigers and insurgent Sinhalese. On the other hand, the novel mainly focuses on Anil’s transnational identity. The novel reflects different reasons for Anil to carry transnational identity: the dissolution of boundaries and crossborder activities, her return to the home country, her connection to the home country, her sense of loss and displacement, and the conflict between national and transnational.